Product Categorization in a Marxian–Capitalist Market Structure: Addressing Food Fraud and Ethical Reinforcement in Nigeria - Bamson, Minaseichinbo (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
While it may well be said that the categorization of product-naming in a capitalist dominated market has its own role, it is also not out of place, from Marxist perspectives, that producers can also deploy the instrument of categorization to rip consumers hard. Against the objectivist view of meaning that categorization as a reference thing directs the interest of the consumers on product content and quality, this study from the capitalist dominated perspectives, avows that categorization of product naming in Nigeria is often times used by producers to corrupt the market desk. Hence the paper, using content analysis of secondary resources, argues that categorization of product is a neuro linguistic activity that many consumers are not at home with. Hence, food fraud has continued to thrive with its subtle usage by producers. To check this, there is need to grow public awareness about it and further more through the means of ethical reinforcement by the state. Thus, the study concludes that the need to amass more wealth can affect producers’ use of certain words as against business ethics.